1991
DOI: 10.1002/etc.5620100110
|View full text |Cite
|
Sign up to set email alerts
|

Acute physiological stress responses of juvenile coho salmon (Oncorhynchus kisutch) to sublethal concentrations of garlon 4®, garlon 3a® and vision® herbicides

Abstract: Juvenile coho salmon (Oncorhynchus kisutch) were exposed for 4 h to sublethal concentrations of the herbicides Garlon 4®, Garlon 3A®, and Vision®. Trials were performed in a closed‐system respirometer that measured oxygen consumption of fish prior to and during a 4‐h exposure. At the end of the exposure period, plasma glucose and lactate concentrations, hematocrit, and leucocrit were measured as indicators of acute physiological stress. There were no biologically significant indications of acute physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 43 publications
3
9
0
Order By: Relevance
“…Even so, our results for resting and maximum oxygen consumption are consistent with previous literature for both juvenile rainbow trout and coho salmon (Janz et al 1991;Scarabello et al 1991Scarabello et al , 1992Myrick and Cech 2000). Scarabello et al (1991Scarabello et al ( , 1992 previously reported oxygen consumption after exhaustive exercise for 3-6-g rainbow trout as 20.1-22.1 mmol h Ϫ1 g Ϫ1 at 15ЊC, which is somewhat higher than in this study ( mmol 17.1 ‫ע‬ 0.4 h Ϫ1 g Ϫ1 at 17ЊC for ∼44-g rainbow trout).…”
Section: Discussionsupporting
confidence: 95%
“…Even so, our results for resting and maximum oxygen consumption are consistent with previous literature for both juvenile rainbow trout and coho salmon (Janz et al 1991;Scarabello et al 1991Scarabello et al , 1992Myrick and Cech 2000). Scarabello et al (1991Scarabello et al ( , 1992 previously reported oxygen consumption after exhaustive exercise for 3-6-g rainbow trout as 20.1-22.1 mmol h Ϫ1 g Ϫ1 at 15ЊC, which is somewhat higher than in this study ( mmol 17.1 ‫ע‬ 0.4 h Ϫ1 g Ϫ1 at 17ЊC for ∼44-g rainbow trout).…”
Section: Discussionsupporting
confidence: 95%
“…2a & 2b), reflecting the normal daily activity pattern (Brett and Zala 1975) of the fish used in our study. The mean fish oxygen consumption value was similar to values reported by other investigations using similar apparatus (MacKinnon and Farrell 1992;Janz et al 1991;Johansen and Geen 1990) indicating that the system could provide reliable oxygen recordings with the newly installed OxyGuard ® DO probes. The DO detecting system was the major modification of the old respirometer whose oxygen consumption data was generated using the averaged readings of four inflow and outflow electrodes (Johansen and Geen 1990).…”
Section: Resultssupporting
confidence: 75%
“…Little is known about the sublethal e!ects of herbicides on "sh. Few studies have examined the e!ects of aquatic herbicides on "sh behavior or physiology (Hildebrand et al, 1982;Janz et al, 1991;Bettoli and Clark, 1992).…”
Section: Introductionmentioning
confidence: 98%